Peace journalism as ideology or peace journalism as a semiotic act of world and life view? - Pieter Jacobus Fourie (Communicare)
In this article it is argued that in the context of critical media and cultural studies’ emphasis on ideology, the accent in understanding peace journalism frequently falls on peace journalism as advocacy journalism and on peace journalism as an ideological manipulation of the representation of war, conflict, terrorism, protest and violence. For an alternative understanding of peace journalism, and in the light of renewed academic interest in the understanding of world and life view as a comprehensive set of values underlying cognition and representation, this article suggests a focus on the description and analyses of the a priori values underlying a journalist’s world and life view and demonstrates how such values may or may not be rooted in a fundamental world and life view predisposed to peace versus violence and war as a solution to conflict. Given world and life view’s emphasis on meaning and meaning-making, the article then suggests an understanding of peace journalism and an understanding among journalists of their work, as a semiotic act and as such signifying and representing the values of world and life views in rhetorical and dialogical ways. Such an understanding and consciousness may lead to heightened journalistic sensitivity regarding how war, violence, conflict and hate are reported. This article deals in consecutive parts with the topics peace journalism, world and life view as a construct and its possible application in the field of peace journalism, and journalism as a semiotic act, characterised by signification, representation, rhetoric and dialogue as four of the main building blocks of journalistic communication, including peace journalism.